Commons manifestos: a reply to Bauwens and Ramos. Issue 2 (3rd April 2018) - Murdock,
Abstract : ABSTRACT This reply piece is a response to the article by Michel Bauwens and Jose Ramos, "Re-imagining the Left through an ecology of the commons: Toward a post-capitalist commons transition". In it, Graham Murdock argues that while developing a commons for contemporary conditions is a core requirement for a post-capitalist social order, it is not in itself sufficient. It is also necessary to confront the contradictory role the state has played in the development of capitalism, as both a force for enclosure and the defence of property rights and the prime guarantor of the public goods and social conditions that facilitate commoning. The rise of neoliberal economic polices has fuelled a new push to enclosure characterized by the privatisation of previously public resources, accelerated corporate concentration, widening income inequalities, and a deepening ecological crisis. The leading digital corporations have played a central role in cementing these processes. Consequently, mobilising digital technologies for commoning requires concerted state action to reverse them and restore the public resources and social conditions that support mutuality.This is a reply to:Bauwens, M., and Ramos, J. 2018. "Re-imagining the left through an ecology of the commons." Global Discourse . https://doi.org/10.1080/23269995.2018.1461442